2018
DOI: 10.4067/s0717-97072018000304068
|View full text |Cite
|
Sign up to set email alerts
|

Coefficient Partition Prediction of Saturated Monocarboxylic Acids Using the Molecular Descriptors

Abstract: Carboxylic acids have clearly been absent from the quantitative structure-property relationship literature. The studies of the quantitative structure-property relationships (QSPR) involve various chemometric methods in which the physico-chemical behavior of a compound is correlated with its structure represented by the structural indices. For example, QSPR methods are applied for the prediction of octanol-water partition coefficient of an organic compound. In this study, the relationship between the octanol/wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…It is reasonable to infer that the correlation is related to the hydrophobicity of organic acids because the partition coefficient of butyric acid (log P = 0.79) is much higher than that of acetic acid (log P = −0.31). 28 This suggests that butyric acid is more readily adsorbed on the SDS-modified surface and thus promotes its consumption.…”
Section: Resultsmentioning
confidence: 99%
“…It is reasonable to infer that the correlation is related to the hydrophobicity of organic acids because the partition coefficient of butyric acid (log P = 0.79) is much higher than that of acetic acid (log P = −0.31). 28 This suggests that butyric acid is more readily adsorbed on the SDS-modified surface and thus promotes its consumption.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 3 coefficients; thus, the order of extraction yield is the same as that of the log K ow values of acetic, propionic, butyric, and valeric acids which are −0.31, 0.25, 0.79, and 1.39, respectively. 43 Additionally, in Figure 3, it can be observed that the extraction performance increases with the S/F ratio in volume. Nevertheless, this increase is more significant in acetic acid extraction in all solvents.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…This trend is because of the hydrophobicity of the acids. Hydrophobicity is related to the octanol/water partition coefficients; thus, the order of extraction yield is the same as that of the log K ow values of acetic, propionic, butyric, and valeric acids which are −0.31, 0.25, 0.79, and 1.39, respectively …”
Section: Results and Discussionmentioning
confidence: 99%